Lignin based phenol resin, and method for preparing thereof

KR103031593B1Active Publication Date: 2026-10-13YUWON CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240106322
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2026-10-13
Estimated Expiration
2044-08-08

Smart Images

  • Figure 112024086632331-PAT00001
    Figure 112024086632331-PAT00001
Patent Text Reader

Abstract

The present invention relates to a lignin-based phenolic resin prepared by comprising the steps of: replacing 30 to 40 weight percent of lignin in 100 weight percent of phenol; adding an acid component and raising the temperature to 80 to 100°C to react for 1 to 3 hours to acid modify the mixture; cooling the acid-modified reaction mixture to 30 to 50°C; adding NaOH and formaldehyde to the cooled mixture and maintaining it at 85 to 90°C for 1 to 1.5 hours; and vacuum dehydrating. In the present invention, an eco-friendly phenolic resin for Bakelite impregnation can be produced by replacing phenol with acid-modified, low-molecular-weight lignin in a certain amount during the synthesis of the phenolic resin. The lignin-based phenolic resin according to the present invention has a curing time, viscosity, and solvent dilution ability suitable for use as a resin for impregnating Bakelite.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a lignin-based phenolic resin and a method for manufacturing the same, and more specifically, to a lignin-based phenolic resin and a method for manufacturing the same that enables the production of an environmentally friendly phenolic resin by replacing phenol with a certain amount of low molecular weight acid-modified lignin during the production of the phenolic resin. Background Technology

[0002] Prepreg, an abbreviation of 'Pre-impregnated material,' refers to an intermediate sheet-type material for fiber-reinforced composites that has been pre-impregnated with resin and reinforcing materials such as paper, cotton fabric, carbon, or glass fibers in a predetermined ratio. Using prepreg offers the advantage of enabling precise control of the resin-to-fiber ratio and allowing for a higher fiber volume ratio in the molded product compared to direct molding methods, thereby enabling the production of high-quality composite parts with high reliability.

[0003] Bakelite, one of these composite materials, is a thermosetting composite material manufactured by impregnating a phenolic resin into a reinforcing material such as paper, cotton cloth, or glass fiber fabric and then curing it at high temperature and high pressure. It has excellent chemical resistance, insulation, and heat resistance, and is currently being applied across various industries as a material for mechanical parts such as automobiles and industrial machinery, or as a material for electrical and electronic components. Recently, its utility has expanded to include heat-resistant parts for steel mills and construction by adding special functionalities such as heat resistance and weather resistance.

[0004] As for prior art regarding such Bakelite, Korean registered patent 10-2671764 presents a Bakelite composite material for electronic components with excellent antistatic properties and a method for manufacturing the same by optimizing a lamination process using conductive nanomaterials.

[0005] Phenolic resins used in Bakelite require functional characteristics such as strength, water resistance, chemical resistance, high density, fixed carbon content, wear resistance, and adhesion depending on the application, but existing phenolic resins have problems such as significant price fluctuations and causing environmental pollution.

[0006] Therefore, in order to reduce carbon emissions, it is necessary to develop alternative materials that can replace phenolic resins. Prior art literature

[0007] Korean Registered Patent 10-2671764 The problem to be solved

[0008] Accordingly, while contemplating how to produce eco-friendly Bakelite in line with consumer demands and global trends, it was determined that lignin consists of a phenylpropane structure, which is an aromatic compound, and that phenolic substances obtained from lignin are not significantly different from substances obtained from fossil fuels in terms of composition and physical properties, thus allowing them to replace phenolic resins, leading to the present invention.

[0009] Accordingly, the objective of the present invention is to provide a lignin-based phenolic resin that can replace the phenolic resin used in Bakelite with a lignin-based phenolic resin by adding lignin, a method for manufacturing the same, and an eco-friendly Bakelite using the lignin-based phenolic resin. means of solving the problem

[0010] The present invention can provide a lignin-based phenol resin prepared by replacing 30 to 40 weight percent of lignin in 100 weight percent of phenol.

[0011] According to one embodiment of the present invention, it is preferable that the lignin has a low molecular weight with a number average molecular weight (Mn) of 2000 to 4000.

[0012] According to one embodiment of the present invention, it is preferable that the lignin be applied in a state dissolved in an organic solvent.

[0013] When the lignin according to the present invention is applied in a state dissolved in a solvent, it is preferable that the viscosity is 30 cps (25°C, solid content 50%) or less and the solvent dilution ability is 350% or more.

[0014] In addition, in the present invention, it is preferable to use the lignin after acid modification.

[0016] The lignin-based phenolic resin according to the present invention can be manufactured by including the steps of: adding lignin and an acid component to phenol and reacting the mixture at a temperature of 80 to 100°C for 1 to 3 hours to acid modify it; cooling the acid-modified reaction product to 30 to 50°C; adding NaOH and formaldehyde to the cooled product and maintaining it at 85 to 90°C for 1 to 1.5 hours; and vacuum dehydrating it.

[0017] According to one embodiment of the present invention, the molar ratio of phenol to formaldehyde is preferably 1:1.1 to 1:1.3.

[0019] In addition, the present invention can provide an eco-friendly Bakelite using the lignin-based phenolic resin as an impregnation resin. Effects of the invention

[0021] According to the present invention, an eco-friendly phenolic resin for Bakelite impregnation can be produced by replacing phenol with acid-modified, low-molecular-weight lignin in a certain amount during the synthesis of the phenolic resin.

[0022] The lignin-based phenolic resin according to the present invention has a curing time, viscosity, and solvent dilution ability suitable for use as a resin for impregnating Bakelite. Specific details for implementing the invention

[0023] The present invention will be described in more detail below.

[0024] The terms used in this specification are for describing specific embodiments and are not intended to limit the invention.

[0025] As used herein, the singular form may include the plural form unless the context clearly indicates otherwise. Additionally, as used herein, “comprise” and / or “comprising” specify the presence of the mentioned features, numbers, steps, actions, parts, elements, and / or groups thereof, and do not exclude the presence or addition of one or more other features, numbers, actions, parts, elements, and / or groups.

[0027] The present invention relates to a lignin-based phenolic resin, a method for manufacturing the same, and an eco-friendly Bekrai using the lignin-based phenolic resin as an impregnation resin.

[0028] The lignin-based phenol resin according to the present invention is prepared by replacing 30 to 40 weight percent of lignin with 100 weight percent of phenol, and the meaning of "lignin-based" includes that which is prepared by replacing a certain amount of phenol used in the manufacture of the phenol resin with lignin, and does not include lignin in a higher amount than phenol in the total 100 weight percent.

[0029] Lignin is an eco-friendly substance produced from black liquor, a byproduct remaining after extracting cellulose and pulp from wood. This lignin consists of a phenylpropane structure, an aromatic compound, and the phenolic substances obtained from lignin do not differ significantly from substances obtained from fossil fuels in terms of composition and physical properties.

[0030] Therefore, in the present invention, by replacing a portion of the phenol, which is a raw material used in the manufacture of phenol resin, with lignin, a natural substance, it is possible to manufacture an environmentally friendly phenol resin while maintaining the physical properties required for the resin used for impregnating Bakelite.

[0031] It is preferable that the lignin according to the present invention be included in a content of 30 to 40 weight percent of the total 100 weight percent combined with phenol to replace phenol, in order to satisfy effects such as viscosity, solvent dilution ability, and curing time.

[0032] In addition, the lignin used in the present invention preferably has a low molecular weight with a number average molecular weight (Mn) of 2,000 to 4,000. If high molecular weight lignin is used outside this range, the viscosity is high in the same solid content, so the solvent dilution ability is low, and thus the physical properties required for the impregnating resin cannot be satisfied, which is undesirable.

[0033] In particular, since the final impregnated resin in the present invention is methanol-based, it is desirable to selectively use lignin with a relatively low molecular weight so that the lignin has high solubility in the organic solvent (MeOH).

[0034] In addition, the acid-modified lignin according to the present invention is preferable in terms of viscosity and solvent dilution ability compared to using crude lignin.

[0035] According to one embodiment of the present invention, the acid used for the acid-modification may preferably be para-toluene sulfonic acid (PTSA), but is not limited thereto.

[0037] The method for manufacturing a lignin-based phenolic resin according to the present invention may comprise the steps of: adding lignin and an acid component to phenol and reacting the mixture at a temperature of 80 to 100°C for 1 to 3 hours to acid modify it; cooling the acid-modified reaction mixture to 30 to 50°C; adding NaOH and formaldehyde to the cooled mixture and maintaining it at 85 to 90°C for 1 to 1.5 hours to produce a phenolic resin; and vacuum dehydrating.

[0038] In addition, when manufacturing phenol resin, the molar ratio of phenol to formaldehyde is 1:1.1 to 1:1.3, which is desirable as it can satisfy the conditions required in the impregnation drying process when used as a resin for impregnating Bakelite, such as a curing time of 70 to 80 sec, a viscosity of 30 cps (25°C, solid content 50%) or less, preferably 20 to 30 cps, and a solvent dilution ability of 350% or more.

[0040] Preferred embodiments of the present invention will be described in detail below. The following embodiments are intended only to illustrate the present invention and should not be interpreted as limiting the scope of the present invention. Furthermore, although specific compounds have been used in the following embodiments, it is obvious to those skilled in the art that equivalents can be used to achieve an equivalent or similar effect.

[0042] Preparation Example 1: Synthesis of Lignin-based Phenolic Resin

[0043] Phenolic resin was synthesized using crude lignin obtained from Moorim P&P Co., Ltd. and StoraEnso as a substitute for >20% of the phenol used, and the specific process is as shown in Table 1 below.

[0044] Ingredients (g) Content mol Synthesis process 1 Phenol 150 1.6 Add raw materials 1-4 and stir 2 Kraft Lignin (Murim) 38 - Maintain temperature at 90℃ for 2.5 hours 3 Formaldehyde (37%) 168 2.1 Vacuum dehydration, dehydration amount 100g 4 NaOH (Aq. 25%) 15 Input raw material 5 5 MeOH 170 packaging

[0046] Experimental Example 1: Evaluation of physical properties as an impregnation resin

[0047] The properties of the synthesized lignin (phenol replacement rate 20%)-based phenolic resin as an impregnation resin were evaluated by checking the curing time (150°C), viscosity (25°C, solid content 50%), and solvent dilution ability (methanol) under each condition, and the results are shown in Table 2 below.

[0048] division Lignin manufacturers Amount of lignin applied relative to phenol (weight%) Physical properties item condition unit Measurements 1 Murim P&P 20 Curing time 150℃ sec 72 viscosity 25℃, solid content 50% cps 23 Solvent dilution ability MeOH % 500 2 30 Curing time 150℃ sec 67 viscosity 25℃, solid content 50% cps 32 Solvent dilution ability * MeOH % 130 3 StoraEnso 20 Curing time 150℃ sec 71 viscosity 25℃, solid content 50% cps 29 Solvent dilution ability MeOH % 550 4 30 Curing time 150℃ sec 66 viscosity 25℃, solid content 50% cps 38 Solvent dilution ability * MeOH % 140 * Solvent Dilution Capacity (MeOH): The ratio of the maximum amount of solvent at which the synthesized phenol resin dissolves stably (transparently) after adding MeOH.

[0049] As shown in the results of Table 2 above, it was found that the solvent dilution ability of the lignin-based phenol resin significantly decreased at a phenol replacement rate of >30%, and since this is difficult to apply in processes that include a solvent dilution process according to the on-site production impregnation process, it was determined that the lignin (30%)-based phenol resin produced without modification or alteration of lignin lacks compatibility.

[0051] Preparation Example 2: Synthesis of phenolic resin using low molecular weight lignin

[0052] To synthesize lignin-based phenolic resins based on the molecular weight of lignin, lignin was dissolved in an organic solvent (MeOH) to separate lignin with a relatively low molecular weight (2000–3000) and applied to the synthesis. The separated low molecular weight lignin (dissolved in organic solvent) was replaced by 30% of the phenol, and phenolic resins were synthesized according to the composition and process shown in Table 3 below.

[0053] Ingredients (g) Content mol Synthesis process 1 Phenol 150 1.6 Add raw materials 1-4 and stir 2 Kraft Lignin (Enso) 64 - Maintain temperature at 90℃ for 2.5 hours 3 Formaldehyde (37%) 168 2.1 Vacuum dehydration, dehydration amount 65g 4 NaOH (Aq. 25%) 15 Input raw material 5 5 MeOH 170 packaging

[0055] Experimental Example 2: Evaluation of physical properties as an impregnation resin

[0056] Under the same conditions as Experimental Example 1 above, the physical properties of the impregnation resin were evaluated, and the results are shown in Table 4 below. To compare with the use of low molecular weight lignin, crude lignin (average molecular weight 3000~4000) was used as a control.

[0057] division Lignin manufacturers Amount of lignin applied relative to phenol (weight%) Physical properties item condition unit Measurements control group Crude Lignin (Enso) 30 Curing time 150℃ sec 66 viscosity 25℃, solid content 50% cps 38 Solvent dilution ability MeOH % 140 Preparation Example 2 Low molecular weight lignin (Enso) 30 Curing time 150℃ sec 73 viscosity 25℃, solid content 50% cps 25 Solvent dilution ability MeOH % 400

[0058] Referring to the results in Table 4 above, when a lignin-based phenolic resin (Preparation Example 1) was synthesized using low molecular weight (organic solvent soluble) lignin (Enso), the results showed improved physical properties as an impregnating resin, such as relatively lower viscosity and higher solvent dilution ability at the same solid content compared to a lignin-based phenolic resin using Crude lignin (Enso) (control group).

[0060] Preparation Examples 3–6: Synthesis of Acid-Modified Lignin-Based Phenolic Resin

[0061] To improve the reactivity of lignin and the storage stability of the final impregnated resin, lignin and phenol were reacted via an acid-modification reaction as shown in Reaction Scheme 1 below, and a lignin (30%)-based phenolic resin was synthesized using the composition (Preparation Example 4) and process shown in Table 5 below. In each preparation example, a lignin (30%)-based phenolic resin was synthesized by acid-modification, while varying the molar ratio of phenol to formalin from 1:1 to 1:1.7 as shown in Table 5 below.

[0062] Reaction Equation 1

[0063]

[0064] Raw materials (parts by weight) Content (g) mol Synthesis process 1 Phenol 150 1.6 Add raw materials 1-3 and stir 2 Kraft Lignin (Enso) 64 Maintain temperature at 90℃ for 2 hours 3 PTSA 15 Cooling to 40℃ and inputting 4-5 parts raw material 4 NaOH (Aq. 25%) 30 Maintain temperature at 85-90℃ for 1~1.5 hours 5 Formaldehyde (37%) 130 1.6 Vacuum dehydration, dehydration amount 50~130g 168 2.1 195 2.4 219 2.7 6 MeOH 175 Raw Material 6 Input and Packaging

[0066] Experimental Example 3: Evaluation of physical properties as an impregnation resin

[0067] Under the same conditions as Experimental Example 1 above, the physical properties of the impregnation resin were evaluated, and the results are shown in Table 6 below.

[0068] division Amount of lignin applied relative to phenol (weight%) Phenol / Formalin Molar Ratio Physical properties item condition unit Measurements Preparation Example 3 30 1 / 1 Curing time 150℃ sec 94 viscosity 25℃, solid content 50% cps 20 Solvent dilution ability MeOH % 520 4 30 1 / 1.3 Curing time 150℃ sec 75 viscosity 25℃, solid content 50% cps 26 Solvent dilution ability MeOH % 450 5 30 1 / 1.5 Curing time 150℃ sec 69 viscosity 25℃, solid content 50% cps 36 Solvent dilution ability MeOH % 280 6 30 1 / 1.7 Curing time 150℃ sec 64 viscosity 25℃, solid content 50% cps 52 Solvent dilution ability MeOH % 160

[0070] Referring to the results in Table 6 above, the optimal conditions for the impregnation drying process are determined to be a curing time of 70 to 80 sec, a viscosity of 20 to 30 cps, and a solvent dilution ability of 300% or more.

[0071] Based on this, the case where the phenol / formalin molar ratio was 1 / 1.3 was the most optimal condition. Synthetic resins with a phenol / formalin molar ratio of less than 1 / 1.3 had too long a curing time, and synthetic resins manufactured with a molar ratio exceeding 1 / 1.3 had too high a viscosity and too low a solvent dilution ability, making them unsuitable as optimal impregnation resins compared to resins with a molar ratio of 1 / 1.3.

[0073] Preparation Examples 7–9: Synthesis of phenolic resin according to lignin replacement ratio

[0074] When synthesizing the phenol resins of Examples 2 to 5 above, the physical properties (curing time, G / T) were confirmed by changing the lignin replacement ratio to 30 to 50 parts by weight relative to the phenol resin, and the results are shown in Table 7 below.

[0075] division Amount of lignin applied relative to phenol (weight%) Phenol / Formalin Molar Ratio Physical properties item condition unit Measurements Preparation Example 7 30 1 / 1.3 Curing time 150℃ sec 75 viscosity 25℃, solid content 50% cps 26 Solvent dilution ability MeOH % 450 8 40 1 / 1.3 Curing time 150℃ sec 72 viscosity 25℃, solid content 50% cps 30 Solvent dilution ability MeOH % 380 9 50 1 / 1.3 Curing time 150℃ sec 64 viscosity 25℃, solid content 50% cps 38 Solvent dilution ability MeOH % 250

[0076] Referring to the results in Table 7 above, in the synthesis of lignin-based phenolic resins by acid modification, the G / T (curing time) tended to be shortened as the lignin replacement ratio increased. While this may be an advantageous factor for the impregnation resin, it also acts as a disadvantage to impregnation (productivity), such as an increase in the viscosity of the impregnation resin and a decrease in solvent dilution ability. Therefore, it was determined that the optimal lignin replacement ratio at the current level of lignin used would be 30–40%.

[0077] In terms of G / T, an excessively short G / T could weaken the adhesion between each prepreg, so it was expected that it would be difficult to synthesize the lignin replacement ratio of the impregnation resin exceeding 40% in order to control the G / T to an appropriate 70~80 sec.

[0078] From the above results, it can be confirmed that by using acid-modified lignin with a low molecular weight, and replacing lignin with 30 to 40 weight percent of phenol in 100 weight percent, considering compatibility (solvent dilution ability) and physical properties (curing time), it has properties suitable for impregnating Bakelite.

Claims

Claim 1 A lignin-based phenol resin prepared by replacing 30 to 40 weight percent of 100 weight percent of phenol with lignin acid-modified using para-toluene sulfonic acid (PTSA) dissolved in methanol, an organic solvent, wherein the lignin has a viscosity of 30 cps (25°C, solid content 50%) or less and a solvent dilution ability of 350% or more. Claim 2 A lignin-based phenolic resin according to claim 1, wherein the lignin has a low molecular weight with a number average molecular weight (Mn) of 2000 to 4000. Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A method for producing a lignin-based phenol resin according to claim 1, comprising the steps of: adding lignin, which has a viscosity of 30 cps (25°C, solid content 50%) or less and a solvent dilution ability of 350% or more when dissolved in methanol, an organic solvent, and para-toluene sulfonic acid (PTSA) as an acid component to phenol and reacting by raising the temperature to 80-100°C for 1-3 hours to acid modify the phenol; cooling the acid-modified reaction product to 30-50°C; adding NaOH and formaldehyde to the cooled product and maintaining the mixture at 85-90°C for 1-1.5 hours at a molar ratio of phenol to formaldehyde of 1:1.1 to 1:1.3; and vacuum dehydration. Claim 7 delete Claim 8 Eco-friendly Bakelite using a lignin-based phenolic resin according to claim 1 as an impregnation resin.

Citation Information

Patent Citations

  • Preparation process of friction-resistant and high-temperature-resistant modified phenolic resin

    CN112011020A

  • Method for producing modified lignin and modified polyphenol, and resin composition material using modified lignin

    JP2023024830A

  • Novolac phenol resin, method for synthesizing the phenol resin and use thereof

    KR1020210142592A

  • Composite materials having good antistatic for electronic parts and method for preparing thereof

    KR1020230062043A